Technostress in engaging open and distance learning: Exploring Malaysian English language lecturers' lived experiences - Ameiruel Azwan Ab Aziz; Noraini Said; Chelster Sherralyn Jeoffrey Pudin; Kamsilawati Kamlun (Global Academic Excellence (M) Sdn Bhd, 2022)
The outbreak of the Covid-19 pandemic has caused a sudden change in the educational landscape globally and shifted traditional face-to-face classes to open distance learning mode. Due to this transition, it is progressively crucial and of great importance to understand the technostress faced by English language lecturers in adopting open distance learning practices. This phenomenological study explores the lived experiences of eleven English language lecturers from three universities in the southern region of Malaysia regarding the technostress faced in open distance learning practice during the pandemic through the lens of Technological Pedagogical Content Knowledge. Fascinatingly, despite the emergency shift to open distance learning, the results have shown that the participants are keen and receptive to the open distance learning deployment. Moreover, due to their Technological Pedagogical Content Knowledge competency, the participants agreed that the technostress experienced is considered manageable and did not affect their work performance. This study's results are hoped to offer insights into understanding the unprecedented phenomenon to ensure positive impacts in tertiary education.